2021
DOI: 10.54386/jam.v23i3.31
|View full text |Cite
|
Sign up to set email alerts
|

Simulating the impact of climate change on sugarcane production in Punjab

Abstract: The present study was performed at three diverse agro-climatic zones of Indian Punjab. A validated DSSAT-CANEGRO model was used to simulate the response of different climate change scenarios on cane yield of four sugarcane varieties (CoPb 91, CoJ 88, Co 118 and Co 238) for each zone. Results described that elevated and lowered minimum temperature upto 3.0°C may alter cane yield by -17.9 to 18.0 per cent. Similarly, ±3.0°C altered maximum temperature may change the cane yield by -17.6 to 17.5 per cent. The suga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 7 publications
1
23
0
2
Order By: Relevance
“…Fetal liver receives most of its blood supply from the umbilical vein, and a great amount of that blood passes the liver in the ductus venosus [43]. On the microanatomical scale, fetal liver contains Fe-rich erythroblastic islets, that are lacking from adult liver [44]. In our study, the levels of non-essential elements in fetal liver were in general either similar (Al, As, Hg, Ni, Pb, Ti, V) or lower (Ba, Cd, Cr, Rb, Sr) compared to maternal liver.…”
Section: Discussionmentioning
confidence: 99%
“…Fetal liver receives most of its blood supply from the umbilical vein, and a great amount of that blood passes the liver in the ductus venosus [43]. On the microanatomical scale, fetal liver contains Fe-rich erythroblastic islets, that are lacking from adult liver [44]. In our study, the levels of non-essential elements in fetal liver were in general either similar (Al, As, Hg, Ni, Pb, Ti, V) or lower (Ba, Cd, Cr, Rb, Sr) compared to maternal liver.…”
Section: Discussionmentioning
confidence: 99%
“…Similarities in preferences for varieties with high yield potential and early maturity Yield and early maturity were generally considered priority attributes across regions (i.e., SEAs, SCAs, WMAfr, ESAfr) and study years (Table 5). For many of these studies, yield and early maturity were jointly considered as most preferred, especially in SCAs (Arora et al, 2019;Burman et al, 2018;Rafiq et al, 2016;Singh et al, 2013;Virk & Witcombe, 2007), WMAfr (Adesina & Seidi, 1995;Horna et al, 2007;Jin et al, 2020), andESAfr (Mogga et al, 2019). For example, Horna et al (2007) suggested that farmers generally prefer varieties with higher potential yield and have shorter days to maturity.…”
Section: 31mentioning
confidence: 99%
“…For example, Horna et al (2007) suggested that farmers generally prefer varieties with higher potential yield and have shorter days to maturity. In some of these studies, preferences for high yield and early maturity were specific to production seasons and ecosystems, that is, for wet season (Rafiq et al, 2016;Singh et al, 2013), dry season (Burman et al, 2018), flood-prone areas (Arora et al, 2019), and upland cultivation (Efisue et al, 2008;Virk & Witcombe, 2007). It was also observed that early maturity may be prioritized over yield 4 in certain growing conditions such as in lowland agroecology (Efisue et al, 2008).…”
Section: 31mentioning
confidence: 99%
“…The principle of sugarcane restructuring is to regulate the planting of superior sugarcane that has the potential for high yield and sugar content according to the cropping pattern, the maturing nature of the variety, the time of harvest, and the milling period of the sugar mills to obtain maximum sugar production [29]. Considering the negative impact of climate change on sugarcane yield [23,[30][31][32][33][34][35], the characteristics that are adaptive to climate anomalies must also be possessed by high-yielding sugarcane varieties that are developed. Examples of these superior varieties are AAS Agribun, ASA Agribun, AMS Agribun, and CMG Agribun, with sugarcane yield of 100-200 tons/ha and sugar content of 11-13%, and sugar crystals 10-20 tons/ha, which were released in November 2017.…”
Section: Policy Alternatives To Increase National Sugar Productionmentioning
confidence: 99%